Evaluation of UK Unit Trust Performance 2001-2006 - Chen, Jizhou (2006)
This paper evaluates the performance of 41 UK equity growth unit trusts for the period between July 2001 and July 2006 by employing traditional performance measures alpha, Sharpe ratio and Treynor ratio. The objective of this paper is to find out whether the 41 actively managed unit trusts have the ability to achieve superior returns over the market. Some evidence of over performance on a risk-adjusted basis by the average fund mangers are found in this study. However, these findings are subject to limitations in terms of transaction and management expenses, the issue of upward biased measurement in the risk-free rate of interest and survivorship bias. Once these caveats are taken into account in calculating risk-adjusted returns, the result may be altered.